Pengaruh Penggunaan Gadget untuk Menarik Minat Belajar Siswa di SMP Cahaya Qur'an Tritunggal, Babat, Lamongan - Lina fauziah; Richa Dwi Rochmatin; Ahmad Dzul Fiqor Abdillah (AJER: Advanced Journal of Education and Religion, 2025)
The development of the times has made very significant changes with the existence of very sophisticated communication tools, namely gadgets, the existence of these tools can result in advantages and disadvantages for a person, one of which is for students. This research aims to analyze the influence of using gadgets to attract students’ interest in learning at Cahaya Qur’an Middle School. This research uses qualitative methods with data collection techniques through observation, interviews and documentation. The results of this research show that the use of gadgets at Cahaya Qur’an Middle School has a significant impact on students’ interest in learning, both positive and negative. Proper use of gadgets can increase students’ interest in learning through easy, interactive and fun access to information. However, excessive use of gadgets can cause addiction and reduce social interaction between students. In this case, the role of the teacher is very important in guiding students so that they can make good use of gadgets in order to support a productive learning process to attract students’ interest in learning.